2020
DOI: 10.3390/molecules25081786
|View full text |Cite
|
Sign up to set email alerts
|

Cymbopogon Proximus Essential Oil Protects Rats against Isoproterenol-Induced Cardiac Hypertrophy and Fibrosis

Abstract: Cymbopogon proximus (Halfabar), a wild plant that is usually used in folk medicine due to its diuretic and antispasmodic effects, was shown to exhibit several cardiovascular protective actions such as antidiabetic, antihypertensive, antioxidant, and antinflammatory effects. However, no reports are available regarding the investigation of the role of Cymbopogon proximus essential oil on cardiac hypertrophy. Therefore, the goals of the present study were to find whether Cymbopogon proximus could alleviate isopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In agreement with this, piperitone, elemol, α eudesmol, limonene, and βeudesmol are reported to be the main components of Cymbopogon proximus [15]. Interestingly, the essential oil of Cymbopogon proximus sprouts has been previously investigated for its cardio-protective effects [19]. Additionally, essential oils from Cymbopogon Flexuosus Steud.…”
Section: Laser Treatment Increased the Levels Of Essential Oils In Cymbopogon Proximus Sproutssupporting
confidence: 52%
See 2 more Smart Citations
“…In agreement with this, piperitone, elemol, α eudesmol, limonene, and βeudesmol are reported to be the main components of Cymbopogon proximus [15]. Interestingly, the essential oil of Cymbopogon proximus sprouts has been previously investigated for its cardio-protective effects [19]. Additionally, essential oils from Cymbopogon Flexuosus Steud.…”
Section: Laser Treatment Increased the Levels Of Essential Oils In Cymbopogon Proximus Sproutssupporting
confidence: 52%
“…On the other hand, the laser-treated sprouts showed slight increases in the levels of linalool (65%), linalyl acetate (64%), and bourbobene (63%) in comparison to the control group. In a recent study, the essential oils elemol, piperitone, α-eudesmol, and β-eudesmol, separated from Cymbopogon proximus sprouts, were able together to protect rats against isoproterenolinduced cardiac hypertrophy and fibrosis [19]. In agreement with this, piperitone, elemol, α eudesmol, limonene, and βeudesmol are reported to be the main components of Cymbopogon proximus [15].…”
Section: Laser Treatment Increased the Levels Of Essential Oils In Cymbopogon Proximus Sproutsmentioning
confidence: 57%
See 1 more Smart Citation
“…The pathological progress of cardiac hypertrophy is accompanied by disorder expressed genes. ANP, BNP, and β-MHC are suggested to be the most consistent markers for cardiac hypertrophy [ 3 , 17 ]. Moreover, aging promoted-cardiac fibrosis is the characteristic of age-related cardiac decline including cardiac hypertrophy [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, aging is suggested to be a major risk factor for varieties of diseases. It is reported that cardiovascular diseases (CVDs) (including hypertension, cardiac hypertrophy and heart failure) contribute to about 31% of all deaths worldwide [ 3 ]. In fact, CVDs have already been the major health problems in both developed countries and developing countries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%